1992
DOI: 10.2527/1992.703798x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lamb age, muscle type, and 24-hour activity of endogenous proteinases on postmortem proteolysis1

Abstract: The objectives of this study were to examine the amount of postmortem proteolysis in three different lamb muscles at different ages and to determine whether a relationship exists between the extent of myofibrillar degradation and certain endogenous proteinase activities. Wether lambs were slaughtered at 8 (n = 6) and 26 (n = 6) wk of age. Samples were taken from the longissimus (LM), gluteus medius (GM), and supraspinatus (SS) muscles for determining myofibrillar fragmentation index (MFI) at 1 and 7 d postmort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 17 publications
(26 reference statements)
8
27
0
Order By: Relevance
“…Moreover, values for muscle fibre area presented in this study are similar to previous results from cross breed wethers age 182 days (Whipple and Koohmaraie, 1992), Dorset wethers, age 159-177 days and crossbreed market lambs . In a recent study in lambs, the authors reported that nutrient restriction during early gestation seemed to affect hyperplasia of the muscle cells, whilst a restriction later in gestation resulted in lighter muscles, in keeping with lighter birth weights cf.…”
Section: Lamb Production Performancesupporting
confidence: 91%
“…Moreover, values for muscle fibre area presented in this study are similar to previous results from cross breed wethers age 182 days (Whipple and Koohmaraie, 1992), Dorset wethers, age 159-177 days and crossbreed market lambs . In a recent study in lambs, the authors reported that nutrient restriction during early gestation seemed to affect hyperplasia of the muscle cells, whilst a restriction later in gestation resulted in lighter muscles, in keeping with lighter birth weights cf.…”
Section: Lamb Production Performancesupporting
confidence: 91%
“…In this way, Whipple and Koohmaraie (1992) examined the amount of post-mortem proteolysis in three different lamb muscles and concluded that degradation products derived from TnT in supraspinatus, a slow type muscle, were distinct from those in longissimus and gluteus medius, fast type muscles. On the other hand, Muroya, Nakajima, and Chikuni (2003), established that slow-oxidative muscles were richer in slow TnT isoforms than were the fast muscles.…”
Section: Contribution Of Endopeptidases: Cathepsins and Calpainsmentioning
confidence: 99%
“…Studies in maturing sheep report an increase muscle fibre area in both glycolytic and oxidative muscle fibres (Whipple and Koohmaraie, 1992). Brandstetter et al (1998) found young growing bulls expressed proportionally more slow type 1 myofibres as they matured.…”
Section: Introductionmentioning
confidence: 99%